Answer:
Step-by-step explanation:
[tex]\dfrac{x}{2}=\dfrac{y}{3}\\\\[/tex]
Cross multiply,
3x = 2y ------------(I)
[tex]\dfrac{y}{4}=\dfrac{z}{4}\\\\4*\dfrac{y}{4}=\dfrac{z}{4}*4\\\\y=z[/tex]
y = z --------------(II)
Plugin y =z in (I)
3x = 2z
3x/2 = z ----------------(III)
x + 2y - z = 10
From (I) and (III)
[tex]x + 3x - \dfrac{3x}{2}=10\\\\4x - \dfrac{3x}{2}=10\\\\Multiply \ the \ entire \ equation \ by \ 2\\\\2*4x - 2*\dfrac{3x}{2}=10*2\\\\8x - 3x = 20\\\\5x = 20[/tex]
Divide both sides by 5
x = 20/5
x = 4
Plugin x = 4 in (I)
3*4=2y
12 = 2y
2y = 12
y = 12/2
y = 6
z = y
z = 6